Implementasi Implementasi Metode Jigsaw dalam Pembelajaran Maharah Qira’ah di MA Walisongo Kelas XII B Sumberejo Purwosari Pasuruan - Rinda, Wahyu Rindayani; Syaiful Rizal, Hasan (Yayasan Daarul Qimmah Gorontalo, 2024)
MA walisongo is one of the madrasas that has Arabic as a subject, but many students do not understand the material provided by the teacher due to students who are rarely active in the learning process. The purpose of this research is, (1) to find out the implementation of the jigsaw method in learning maharah qiroah. (2) What are the advantages and disadvantages of the jigsaw method. This study uses a qualitative research design with participants from the MA Walisongo school from a madrasa in the Sumberejo Pasuruan area. The jigsaw method is implemented in maharah qira'ah learning for one academic semester. Data was collected through observation and interviews. Data analysis was performed using a qualitative descriptive approach. The results showed that the implementation of the jigsaw method in maharah qira'ah learning had a positive impact that the implementation of the jigsaw method in maharah qira'ah learning at MA Walisongo had been implemented quite well, most of the students had increased their reading of Arabic using the jigsaw method. The advantage in the process of implementing the jigsaw method in learning mahara qira'ah at MA Walisongo is that the jigsaw method is more effective than the lecture method, enabling students to understand the material. While the shortcomings in the process of implementing the jigsaw method in learning maharah qira'ah at MA Walisongo are that it requires quite a long time in the learning process.